In vitro toxicity assessment of nanocrystals in tissue‐type cells and macrophage cells. Issue 5 (15th December 2017) - Chen, Meiling; Li, Ying; Zhou, Jiezhao; Yang, Zhenbo; Wang, Zhiyuan; Yang, Yang; Zhang, Hui; Li, Zhiping; Mei, Xingguo
Abstract: Nanocrystals (NCs), a type of innovative material particle, are a potential drug delivery platform that aims to improve the bioavailability of hydrophobic drugs. However, due to the lack of consideration of their toxicity, existing studies have not investigated whether the nanoscale properties of NCs, such as particle sizes, may lead to NC‐induced toxicity. Because of the disparity between the rapid development of NCs and the lack of studies regarding NC toxicity, the present study investigated possible NC toxicity and clarified the relationship between particle sizes and NC toxicity. RAW264.7 and HepG2 cells were chosen as representatives of macrophage cells and tissue‐type cells, respectively. Monosodium urate NCs were used as a drug model. Different particle sizes of monosodium urate NCs were prepared using precipitation methods. Methyl tetrazolium, lactate dehydrogenase, oxidative stress and apoptosis/necrosis assays were then used to evaluate cell damage and recovery. The results showed that small NC particle sizes produced higher toxicity than larger ones. In immune cells, these cytotoxic effects were greater than in tissue cells. After removal of small NCs, tissue cell damage could be significantly reversed, while immune cells were only slightly restored. However, after removal of large NCs, both cell types had almost no recovery. In summary, despite conventional wisdom, our research confirmed that NCs are not very safe and that NC particle sizes are closely related to the degree of NC toxicity. Abstract : Nanocrystals (NCs) are a potential drug delivery platform. However, existing studies have not investigated whether the nanoscale properties of NCs might lead to toxicity. In this study, monosodium urate NCs were used as a drug model to investigate possible toxicity and to clarify the relationship between particle sizes and NC toxicity. Our research confirmed that NCs were unsafe and that particle sizes were closely related to the degree of NC toxicity.